The role of DPP6 dysregulation in neuropathology: from synaptic regulation to disease mechanisms - Ding, Xuan-Yan; Habimana, Jean de Dieu; Li, Zhi-Yuan (Frontiers in Cellular Neuroscience, 2025)
As a transmembrane protein, DPP6 modulates the function and properties of ion channels, playing a crucial role in various tissues, particularly in the brain. DPP6 interacts with potassium channel Kv4.2 (KCND2), enhancing its membrane expression and channel kinetics. Potassium ion channels are critical in progressing action potential formation and synaptic plasticity. Therefore, dysfunction of DPP6 can lead to significant health consequences. Abnormal DPP6 expression has been identified in several diseases, such as amyotrophic lateral sclerosis (ALS), autism spectrum disorder (ASD), spinal bulbar muscular atrophy (SBMA), and idiopathic ventricular fibrillation. Recent research has indicated a connection between DPP6 and Alzheimer’s disease as well. The most common symptoms resulting from DPP6 dysregulation are mental deficiency and muscle wastage. Notably, these symptoms do not always occur at the same time. Besides genetic factors, environmental factors also undoubtedly play a role in diseases related to DPP6 dysregulation. However, it remains unclear how the expression of DPP6 gets regulated. This review aims to summarize the associations between DPP6 and neurological diseases, offering insights as well as proposing hypotheses to elucidate the underlying mechanisms of DPP6 dysregulation.